THE ANTHROPOGENIC AND CLIMATE APOCALYPSE IN MICHAEL CRICHTON’S STATE OF FEAR: AN ECOCRITICAL STUDY - AHMED, SHOKHAN RASOOL (Journal of Duhok University, 2023)
State of Fear (2004) by Michael Crichton (1942-2008) is an ecocriticism novel that delves into the sensitive topic of climate change. The ecocritical approach considers nature as a prevalent factor through the belief that natural forces widely determine human evolution as a community. According to ecocritics, the human world is not developed solely by linguistic and social factors (Milner 2022, p. 18). The two elements are just among the many aspects accountable for the presence and progress of people. Generally, life, including human life, is extremely influenced by the functions of nature and the environment. Therefore, according to the ecocriticism theory, nature is a critical element of human life. After changing into the discipline of theory, eco-criticism was divided into sections. One of the parts developed into reviewing and interpreting the functions of nature, images, and natural items in the literacy works generated by scholars worldwide. Ecocriticism assumes a prominent position within the realm of literary studies due to its capacity to explore and elucidate the inherent ecological distinctions among various geographical settings. However, the main source of thoughts, study, and results in ecocritical research will always come from the authors and poets who are famous and well-developed in literature (Hansen 2020, p.146). Using an Ecocritical approach, the paper seeks to apply Michael Crichton's concepts of the environment through global warming. The paper aims to determine the relationship between literature and scientific data on global warming. Moreover, it analyzes the significant concepts of the novel State of Fear to develop a clear understanding of the author's perception and political ideologies concerning global warming. It also seeks to ascertain future global warming effects' validity